On Fundamental Trade-offs of Device-to-Device Communications in Large Wireless Networks - Altieri, Andrés Oscar (2015)
This paper studies the gains, in terms of served requests, attainable through out-of-band device-to-device (D2D) video exchanges in large cellular networks. A stochastic framework, in which users are clustered to exchange videos, is introduced, considering several aspects of this problem, i.e., the video caching policy, user matching for exchanges, and aspects regarding scheduling and transmissions. A family of admissible protocols is introduced: in each protocol the users are clustered by means of a hard-core point process and, within the clusters, video exchanges take place. Two metrics, quantifying the 'local' and 'global' fractions of video requests served through D2D are defined, and relevant trade-off regions involving these metrics, as well as quality-of-service constraints, are identified. A simple communication strategy is proposed and analyzed to obtain inner bounds to the trade-off regions and to draw conclusions on the performance attainable through D2D. To this end, the analysis of the time-varying interference that the nodes experience and the tight approximations of its Laplace transform are derived.